Structural organization in 9-year-old HIV-infected children and HIV-exposed children - Mberi, Farai (Department of Human Biology, 2024)
Despite early initiation of antiretroviral treatment (ART) in children, studies continue to report HIVrelated neurodevelopmental damage and delays. Neuroimaging and neuropsychological studies have identified brain regions and cognitive domains vulnerable to the effects of HIV infection and exposure in children. As most studies focus on a single time point, it is unclear if the HIV-related abnormalities reported represent damage or developmental delay. Follow up studies are needed to better understand the long-term consequences of HIV in the ART era. Further, few studies examine links between brain imaging and cognitive outcomes, which provides a better understanding of the consequences of imaging abnormalities. This thesis includes a follow up study of a Cape Town-based cohort using neuroimaging, neurocognitive and clinical data at age 9 – 10 years. The cohort includes Children Perinatally infected with HIV (CPHIV) from the Children with HIV Early antiRetroviral (CHER) trial, who initiated ART by the age of 2 years. In addition, the cohort includes a control group made up of Children who are HIV Uninfected (CHU) and Children HIV-exposed, but Uninfected (CHEU). The age group in this study represents the beginning of adolescence, a critical period for the maturing brain. In particular, white matter increases in early adolescence to later stabilize in the middle teenage years. In parallel, this growth is related to maturing cognitive abilities allowing for more complex thinking processes. Diffusion tensor imaging (DTI) measures various aspects of white matter microstructure. DTI data can be explored using different methods, such as voxel wise analysis (VWA) and tractography. Within this cohort, we've previously reported white matter alterations using VWA at ages 5 and 7 years in the inferior/superior longitudinal fasciculus (ILF/SLF), inferior fronto-occipital fasciculus (IFOF), forceps minor, superior corona radiata (SCR), anterior thalamic radiation (ATR) and corticospinal tract (CST), in CPHIV despite early ART, pointing to ongoing HIV related white matter injury associated with myelin loss and axonal degradation. We hypothesize continued diffuse white matter abnormalities in these regions, pointing to chronic damage from at age 5. Tractography quantifies tract properties within the context of gray matter regions, giving functional context to DTI measures. Tractography also allows for the quantification of structural organization measures. Graph theory measures various aspects of brain organization, such as segregation and efficiency. Network measures can identify changes in structural organization due to disease, brain disorders and age. These measures also reflect cognitive and behavioral outcomes. Studies examining structural organization in CPHIV have reported alterations in gray matter volumes affecting local and network properties, suggesting HIV may influence signal propagation. To fill the gap between imaging outcomes and functional consequences within the population of children living with or exposed to HIV, we used tractography to identify the gray matter regions most dependent on tracts affected by HIV and the influence of HIV infection and exposure on white matter organization. Further, we explored possible links between tractography and graph outcomes and neuropsychological measures. Methods: We performed DTI-based VWA and tractography in a cohort of 58 CPHIV, 24 CHEU and 18 CHUU at age 9 – 10 years. Structural measures included DTI parameters, fractional anisotropy (FA), mean diffusivity (MD), axial diffusion (AD) and radial diffusion (RD). Tractography based structural network measures included degree, strength, transitivity, nodal efficiency, and local efficiency as measures of local network properties, and network modularity, global efficiency, and global transitivity as measures global organization. Statistical analysis was performed to identify HIV infection and exposure related differences, as well as explore relationships between imaging outcomes and neuropsychological data. Results: In the DTI voxelwise analysis, we observed higher MD in the IFOF, ILF/SLF, SCR and forceps minor of CPHIV. Many changes in MD were attributed to above-normal RD and/or AD which point to demyelination and axonal degradation. Furthermore, some regional HIV mediated white matter abnormalities characterized by higher MD were associated with markers of early immune compromise, including CD4% around age 12 weeks and timing of disease severity (age at nadir CD4%). Using DTI tractography, we observed that tracts with higher mean MD, AD and/or RD included seeds with connections to the insula, putamen, and fronto-temporoparietal regions. Tracts with higher MD, AD and/or RD were within the same hemisphere, with the exception of one interhemispheric connection of higher AD between insula and right caudate. Across participants, higher MD and RD in frontotemporoparietal connections were associated with lower performance in sequential processing, which measures auditory working memory. Among CHU, we found significant negative correlations between sequential processing and MD in basal ganglia connections to limbic and fronto-parietal regions. Among CPHIV, we found significant negative correlations between sequential processing and MD in a handful of tracts connecting regions in the limbic and temporoparietal junction. Lastly, in the graph theory-based analysis we found lower degree in the inferior temporal gyrus in CPHIV compared to CHU. Further, nodal degree in the inferior temporal gyrus across study participants was associated with auditory working memory. We did not find any HIV exposure effects on DTI measures. Conclusions: The DTI results presented in this thesis indicate persistent localized white matter damage or delayed development in CPHIV, with some regions influenced by early immune health. In addition, we observe a robust global network despite disconnections in tracts connecting the inferior temporal gyrus of CPHIV. Long term axonal loss and demyelination may result in hypomyelinated axons that are loosely packed in the now widened extra-exonal space. Further, white matter connectivity in frontotemporoparietal and limbic regions as well as nodal disconnections in the inferior temporal gyrus was associated with auditory working memory among CPHIV, suggesting these abnormalities contribute to deficits in this domain. In CPHIV, we observe typical networks that are robust to the effects of altered connectivity among regions of the temporoparietal cortex, limbic and subcortical areas. Lastly, we observe no HIV exposure effects on white matter integrity and network measures suggesting differences reported at 7 years in this cohort have resolved.